2007
DOI: 10.1111/j.1447-0349.2007.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Take my hand, help me out’: Mental health service recipients' experience of the therapeutic relationship

Abstract: The purpose of this study was to describe mental health service recipients' experience of the therapeutic relationship. The research question was 'what is therapeutic about the therapeutic relationship?' This study was a secondary analysis of qualitative interviews conducted with persons with mental illness as part of a study of the experience of being understood. This secondary analysis used data from 20 interviews with community-dwelling adults with mental illness, who were asked to talk about the experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
170
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(178 citation statements)
references
References 30 publications
5
170
0
3
Order By: Relevance
“…When developed, it implies respect for the particularities and ways of thinking and acting of the other and an effort to help the person gain mastery and realistically face the stressful events of life (17) . Authenticity and honesty are qualities desired in the TR therapy and useful to help people find real solutions to problems (18) . In the theory of interpersonal relationships, it is considered that from the uniqueness of the human design, it is possible to appreciate, understand and accept people as they are, respecting their individualities, limitations and potential (9) .…”
Section: Discussionmentioning
confidence: 99%
“…When developed, it implies respect for the particularities and ways of thinking and acting of the other and an effort to help the person gain mastery and realistically face the stressful events of life (17) . Authenticity and honesty are qualities desired in the TR therapy and useful to help people find real solutions to problems (18) . In the theory of interpersonal relationships, it is considered that from the uniqueness of the human design, it is possible to appreciate, understand and accept people as they are, respecting their individualities, limitations and potential (9) .…”
Section: Discussionmentioning
confidence: 99%
“…These researchers concluded that when nurses are able to signal they have noticed what is being said and the person feels heard individuals are able to open up to perspectives on their experiences that they might not have considered. In this light connecting with an individual's experience via mentalizing, particularly when accompanied by a respectful, genuine and a nonjudgemental attitude is a preliminary step to exploring with individuals how they make sense of their experiences [32,33] .…”
Section: The Process Behind the Mirror: Mentalizationmentioning
confidence: 99%
“…Individuals in recovery have told researchers about their relationships with PMH nurses; both ones where they had a sense of openness and trust and ones where they experienced clinicians as detached [24,33] . These individuals said they needed an authentic relationships as well as validation and support for their experiences.…”
Section: Beyond Engagement: What Happens From Herementioning
confidence: 99%
“…A large proportion of patients and their families who are seeking help for their mental illness rightfully expect the hospital and nursing staff to be aware of their needs and treat them sympathetically as unique individuals without any bias and discrimination. 2 Worldwide, it is an ongoing concern that the subject of psychiatry, psychiatrists, mental health professionals and the mentally ill patients are severely affected by the negative biases and the cultural stereotypes of the general public.…”
Section: Introductionmentioning
confidence: 99%